The Windows NT web server handbook - Sheldon, Thomas (Osborne McGraw-Hill, 1996)
Microsoft is positioned to make a huge impact with its Internet Information Server. In order to remain competitive on the Web, keeping up with Microsoft's Internet technologies is imperative. In a fast-paced world, you need tactical how-to information that allows you to quicky and easily ramp up with the latest developments. The Windows NT Web Server Handbook is well-timed to arrive just as interest in this Internet Information Server is building, and it's packed with the necessary answers to help you get up to speed with this major new offering.